Travel blogging between personal staging and commercial alignment – a conceptual framework - Nora Winsky; Julia Dickow (Via@)
Due to recent changes in the blogosphere, and in travel blogging in particular, there is a need to reflect on travel blogs as complex media. In this article, commodification and professionalization processes, as well as the specific situatedness of travel blogs at the interface of on- and offline worlds, are taken into account in order to present a differentiated and adaptable conceptual framework for analyzing travel blogs. Within this framework, blogs are situated between personal staging and commercial alignment. The paper shows, how the use of different blogging practices (such as sharing and recommending travel experiences) allows bloggers to construct and use different web-identities simultaneously. By using close and wide readings, it is demonstrated how playing the role of connoisseur of a tourist city and online friend (personal staging) enables bloggers to establish a profitable travel blog and be effective with their marketing strategies (commercial alignment). A case study of travel blogs relating to Barcelona serves as an illustrative example and confirms the suitability of this conceptual approach.